An inter‐story drift‐based parameter analysis of the optimal location of outriggers in tall buildings. (24th September 2015) - Zhou, Ying; Zhang, Cuiqiang; Lu, Xilin
Summary: Outriggers are usually added in structural systems of tall buildings to collaborate central shear walls with peripheral columns. With outriggers, the structural overturning moment can be balanced, and the inter‐story drift can be controlled under horizontal loads. Therefore, the optimal location of outriggers plays a very important role in controlling the behavior of the whole building. Existing research has focused on the optimal position of outriggers on the base of the structural roof deflection. In the engineering practice, however, inter‐story drift is the most important target to control the design of tall building structures. This paper investigates the theoretical method of inter‐story drift‐based optimal location of outriggers. A Matlab program is written to perform the parameter analysis of optimal location of outriggers. Take a 240‐m tall building for a target building, the optimal location of one to three sets of outriggers under wind and earthquakes is obtained and can be utilized for the structural preliminary design of tall buildings. Copyright © 2015 John Wiley & Sons, Ltd.